2024
DOI: 10.4097/kja.23604
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the median and intermediate approaches to the ultrasound-guided sacral erector spinae plane block: a cadaveric and radiologic study

Bilge Olgun Keleş,
Necati Salman,
Elvan Tekir Yılmaz
et al.

Abstract: Background: Erector spinae plane block (ESPB) is a well-established method for managing postoperative and chronic pain. ESPB applications for the sacral area procedures are called sacral ESPBs (SESPBs). This cadaveric study aimed to determine the distribution of local anesthesia using the median and intermediate approaches to the SESPB.Methods: Four cadavers were categorized into the median and intermediate approach groups. Ultrasound-guided SESPBs were performed using a mixture of radiopaque agents and dye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Our clinical experience about this potential mechanism of action was further confirmed by a recent anatomical study. 4 However, in our opinion sacral ESP block shows its key limitation precisely in the unpredictability of the dermatomeric coverage achieved, depending on many factors as the anatomy of the patient and of the fascial compartment, the technique, the level of puncture, the volume of injectate and the type of anesthetic used (including also the potential benefit of the additives). In our opinion this is a crucial consideration when using sacral ESP block for surgery, especially in lower limb and in the cases of major surgery affecting dermatomes above L4.…”
Section: To the Editormentioning
confidence: 90%
“…Our clinical experience about this potential mechanism of action was further confirmed by a recent anatomical study. 4 However, in our opinion sacral ESP block shows its key limitation precisely in the unpredictability of the dermatomeric coverage achieved, depending on many factors as the anatomy of the patient and of the fascial compartment, the technique, the level of puncture, the volume of injectate and the type of anesthetic used (including also the potential benefit of the additives). In our opinion this is a crucial consideration when using sacral ESP block for surgery, especially in lower limb and in the cases of major surgery affecting dermatomes above L4.…”
Section: To the Editormentioning
confidence: 90%
“…In genitourinary surgeries, SESPB has been applied by the midline approach and single injection, and successful results have been obtained [ 20 , 21 , 22 , 23 ]. In a cadaveric study, we have demonstrated that the radiopaque substance administered with the midline SESPB method passes to the anterior region of the sacrum and the involvement of the S2 to S5 nerves with Computed Tomography [ 24 ]. We also utilized the findings of our cadaveric study in planning this study.…”
Section: Discussionmentioning
confidence: 99%